Bookhive: Virtual Society for Readers - S, Amitha Madhav C; A, Mohammed Hussain; T, Muhammed Favas E; V, Muhammed Shaheer P; C, Shishira M (Journal of Ubiquitous Computing and Communication Technologies, 2024)
In an era marked by technological advancements, the research endeavors to revolutionize the traditional paradigm of library management by introducing a comprehensive virtual society for readers enriched with digital features and user-centric functionalities. This system comprises multiple interconnected modules designed to enhance the overall library experience for both administrators and patrons. The core Library Management Module streamlines book cataloging, user management, and inventory tracking, optimizing the operational efficiency of libraries. Concurrently, the Mobile App Module extends the library’s reach beyond physical boundaries, offering a user-friendly platform for on-the-go access to resources, virtual book clubs, and personalized recommendations. The Community Engagement Module fosters a vibrant literary community by facilitating discussions, author-reader interactions, and collaborative book recommendations. The Delivery and Rare Books Module ensures accessibility by enabling users to request book deliveries and notifying them of rare book availability. Furthermore, the User Profile and Customization Module empowers patrons to personalize their library experience, from user registration to preference settings. This research is not merely a technological overhaul but a gateway to a more dynamic and inclusive library ecosystem, embracing the digital age while preserving the essence of community, engagement, and the joy of reading. With data-driven insights, personalized features, and an emphasis on community building, our Library Management System represents a forward-looking approach to redefining the role of libraries in the modern world, ensuring they remain vibrant hubs of knowledge, connection, and literary exploration.
Keywords: Library; Online Community; Interface; Books; social media; Community; Book Lending Platform